2017
DOI: 10.7454/uiphm.v1i0.35
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Kaempferia Galanga Linn Rhizome's Extract Towards the Healing of Minor Recurrent Aphthous Stomatitis in RSGMP USU's Patients

Abstract: Objective: This study aimed to explain the nursing care of the elderly with impaired physical mobility through joint exercise intervention, such as performing the Muslim prayer movement or Salat. Methods:The quasi-experimental study examined the effect of Muslim prayer movement on elderly with impaired physical mobility. Muslim prayer movements were performed for 5 weeks, once a day, and the materials used were an MP3 player, a stopwatch, and a goniometer.Results: Evaluation using Berg Balance Test showed an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Ethyl- p -methoxycinnamate (EPMC) is one of the bioactive substances contained in KG extract in large quantities. EPMC isolated from KG extract has activity against Mycobacterium tuberculosis and Candida albicans [ 5 ]. Umar et al (2014) have confirmed the anti-inflammatory effects of EPMC on mouse and human macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethyl- p -methoxycinnamate (EPMC) is one of the bioactive substances contained in KG extract in large quantities. EPMC isolated from KG extract has activity against Mycobacterium tuberculosis and Candida albicans [ 5 ]. Umar et al (2014) have confirmed the anti-inflammatory effects of EPMC on mouse and human macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin biosynthesis increases in inflamed tissues and becomes a marker of acute inflammatory processes [ 7 , 8 ]. The inhibition of COX-2 by EPMC conduces an anti-inflammatory effect [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 Meanwhile, another clinical trial of topical K. galanga extract on 16 patients with recurrent aphthous stomatitis has showed good results in reducing the ulcer size and pain. 31 …”
Section: Introductionmentioning
confidence: 99%
“…The extract of kencur rhizomes (Kaempferia galanga L.) contains ethyl-p-methoxycinnamate (EPMS) that has an anti-inflammatory and analgesic (Riasari et al, 2016;Tambunan & Lubis, 2017;Umar et al, 2012) antidiabetic (Ernawati et al, 2017) and antioxidative effects (Riasari et al, 2016). EPMS is a lipophilic compound and low water solubility, resulting in low systemic bioavailability (Ekowati et al, 2017).…”
Section: Introductionmentioning
confidence: 99%